Please baby please [videorecording (DVD)] - Kramer, Amanda (Director); Taylor, Noel David; Riseborough, Andrea, 1981-; Melling, Harry, 1989-; Moore, Demi; Glusman, Karl, 1988- (Music Box Films, 2023)
Lower East Side bohemian couple Suze and Arthur become obsessed with a sadistic greaser gang, arousing previously unexplored desires and leading them to question the confines of gender, monogamy, and the sexual status quo.